Kruppel acts as a developmental switch gene that mediates Notch signalling-dependent tip cell differentiation in the excretory organs of Drosophila. - Hoch, M.; Jackle, H. (The EMBO Journal, 1998)
Cell proliferation in the excretory organs of Drosophila, the Malpighian tubules (MT), is under the control of a neural tip cell. This unique cell is singled out from equivalent MT primordial cells in response to Notch signalling. We show that the gene Krüppel (Kr), best known for its segmentation function in the early embryo, is under the control of the Notch-dependent signalling process. Lack-of-function and gain-of-function experiments demonstrate that Kr activity determines the neural fate of tip cells by acting as a direct downstream target of proneural basic helix-loop-helix (bHLH) proteins that are restricted in response to Notch signalling. We have identified a unique cis-acting element that mediates all spatial and temporal aspects of Kr gene expression during MT development. This element contains functional binding sites for the restricted proneural bHLH factors and Fork head protein which is expressed in all MT cells. Our results suggest a mechanism in which these transcription factors cooperate to set up a unique cell fate within an equivalence group of cells by restricting the activity of the developmental switch gene Kr in response to Notch signalling.